2005
DOI: 10.1007/s00436-005-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

Study on morphology, pathogenicity, and genetic variability of Beauveria bassiana isolates obtained from Boophilus microplus tick

Abstract: Fifty isolates of Beauveria bassiana (Balsamo) Vuillemin, 1912 (Ascomycota: Clavicipitaceae) were analyzed by morphology, for their pathogenic potential to Boophilus microplus (Canestrini, 1887) (Acari: Ixodidae) larvae, and by Random Amplified Polymorphic DNA-Polymerase Chain Reaction technique. Morphological analysis demonstrated that isolates present characteristics compatible to those described for B. bassiana in the literature. Virulence test demonstrated that all isolates present lethal effect on larvae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 21 publications
1
16
1
4
Order By: Relevance
“…In line with this suggestion, high genetic variability has been demonstrated among entomopathogenic fungi, and the level of polymorphism can be highly variable even within the same species (FERNANDES et al, 2006). Thus, the isolates of genus Beauveria presented higher activity against the ampul, and it can be concluded that the Unioeste 44 isolate show great potential for the control of G. spegazziniana.…”
Section: Molecular Characterizationmentioning
confidence: 70%
“…In line with this suggestion, high genetic variability has been demonstrated among entomopathogenic fungi, and the level of polymorphism can be highly variable even within the same species (FERNANDES et al, 2006). Thus, the isolates of genus Beauveria presented higher activity against the ampul, and it can be concluded that the Unioeste 44 isolate show great potential for the control of G. spegazziniana.…”
Section: Molecular Characterizationmentioning
confidence: 70%
“…Tais divergências podem ser explicadas pelo elevado grau de variabilidade genética exibida pelos fungos entomopatogênicos, pois mesmo dentro de uma determinada população, o nível de polimorfismo entre os isolados pode ser altamente variável (SOSA-GÓMEZ; TIGANO; ARANTES, 1998;FERNANDES et al, 2006). Além disso, os isolados utilizados no referido trabalho não foram os mesmos utilizados no presente estudo.…”
Section: Caracterização De Isolados De Beauveria Bassiana Por Rapdunclassified
“…Different isolates have been used to control arthropods that affect livestock (FERNANDES et al, 2006) and crops (ALVES, 1998). Other studies have assessed this species' genetic variability and geographic distribution (FERNANDES et al, 2006;FERNANDES et al, 2009), interaction with chemical insecticides (McCOY & TIGANO-MILANI, 1992), tolerance to stress conditions and performance (FERNANDES et al, 2007), enzymatic activity, production of toxins and action on beneficial arthropods, animals and humans (ZIMMERMANN, 2007).…”
Section: Introductionmentioning
confidence: 99%